Implementasi Akhlak Kepada Allah Dalam Kehidupan Mahasiswa Sehari-Hari - Muhammad Iqbal Ramadhan; Fathurrahman Fathurrahman; Muhammad Taura Zilhazem; Abdul Ganif Herlambang; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
Of the many students today, many of them have forgotten their obligations as God's creatures. If left unchecked, it is feared that negative things will arise for students. So it is very important to instill the values of moral education in every student. This research was made with the aim of knowing the implementation of morals to the Creator in the daily lives of students. The method used in this research is a qualitative descriptive approach, which is in the form of a questionnaire and literature study. The subjects in this research were 30 active students in semesters 1-8 at public and private universities. Etymologically, morality means character, character, and behavior. What is meant by morality to God is the act that should be done by God's servant (His creatures) to the Creator. It can be said that morality towards Allah is when one acknowledges and realizes that there is no God except Allah SWT. (Noble) moral behavior towards Allah, namely faith, piety, sincerity, gratitude, repentance, dhikr, prayer and trust. As God's creatures who are so weak and powerless, we as students are encouraged to be moral (noble) to God. From the results of the questionnaire it can be concluded that the majority of students have implemented ethical behavior towards Allah in their lives.